Consumo de sustancias y características sociodemográficas de solicitantes de tratamiento ambulatorio en una red de atención especializada en México; análisis comparativo entre 2007 y 2014 - David Bruno Díaz-Negrete; Alma Delia Gutiérrez-López; Carmen Fernández-Cáceres; Ricardo Sánchez-Huesca (Centros de Integración Juvenil A.C., 2015)
Introduction: the Epidemiological Information System on Drug Abuse of Centros de Integración Juvenil, integrates data from all the treatment seekers in 116 units from the national network. Objective: this work aims to compare sociodemographic and drug abuse patterns in illicit drug users seeking outpatient treatment between 2007 and 2014. Method: data was retrieved from about 170,000 cases, from population attending in 2007 and 2014 (n=18,136 and 21,320, respectively). Analysis included the description of 2007-2014 consumption trends at a national level; comparison of sociodemographic characteristics and consumption patterns of patients initiating treatment in 2007 and 2014; and regional comparison of recent substance use and its average annual growth between these last two years. Results: a significant increase of marijuana, methamphetamines, hallucinogens and ecstasy consumption was detected; meanwhile, cocaine, inhalants and heroin use showed a decrease. A higher percentage of women and children seeking treatment, an earlier drug use onset and a higher level of marijuana reported as onset substance and as drug motivating treatment seeking were also observed. Finally, several regional differences were registered. Discussion and conclusions: these results confirm those reported in population surveys carried out in Mexico regarding the increased use of substances as marijuana and methamphetamine; by contrast, the decline in cocaine, inhalants and heroin use is contrary to the reported in other populations. Despite the limitations of the study, its findings may provide significant information to develop prevention and treatment programs in Mexico.----------------------- Introducción: el Sistema de Información Epidemiológica del Consumo de Drogas de Centros de Integración Juvenil integra datos de la población que solicita tratamiento en las 116 unidades que conforman la red nacional de atención. Objetivo: el presente trabajo compara las características sociodemográficas y de consumo en usuarios de drogas solicitantes de tratamiento ambulatorio entre 2007 y 2014. Método: se recuperó información de cerca de 170 mil casos, principalmente de población atendida entre 2007 y 2014 (n=18,136 y 21,320, respectivamente). El análisis comprendió la descripción de tendencias del consumo 2007-2014 en un nivel nacional; la comparación del perfil sociodemográfico y el patrón de consumo de la población atendida en este periodo; así como la comparación regional del uso reciente de sustancias y de su crecimiento medio anual. Resultados: se observa un aumento significativo del consumo de mariguana, metanfetaminas, alucinógenos y éxtasis, mientras que el uso de cocaína, inhalables y heroína presenta una disminución. Se registra un incremento de mujeres y menores de edad atendidos, una menor edad de inicio y un aumento del consumo de mariguana como droga de inicio y de mayor impacto. Finalmente, se aprecian diversas diferencias regionales. Discusión y conclusiones: los resultados confirman lo reportado en encuestas de México respecto al aumento del uso de mariguana y metanfetaminas, así como la disminución del uso de cocaína, inhalables y heroína, contrario a lo reportado en otras poblaciones. Estos hallazgos proporcionan información relevante para el desarrollo de programas y servicios en México.